Evaluating Malnutrition Practices and Mother's Education on Children Failure to Thrive Symptoms Using Entropy-Weight and TOPSIS Method - Maria Tzitiridou-Chatzopoulou; Georgia Zournatzidou; Eirini Orovou; Maria Lithoxopoulou; Eftychia Drogouti; George Sklavos; Evangelia Antoniou; Christos Tsakalidis (MDPI AG, 2024)
Background/Objectives: Failure to thrive (FTT) is mostly caused by insufficient consumption of nutrient-rich food, recurrent infections like diarrhea and intestinal worms, substandard caregiving practices, and limited availability of health and other vital services. Furthermore, there was a correlation between the educational level of mothers and the occurrence of FTT in children aged 6-12 months. Thus, the objective of the current research is twofold: (i) to investigate other factors related to FTT and (ii) to evaluate the impact of them on FTT in Sub-Saharan African countries and their urban areas. Methods: We used weight entropy and TOPSIS methods to approach the research question. In particular, the entropy-weight method is effective for precisely evaluating the relative significance of the selected criteria for TOPSIS computation. Thus, data were retrieved from the database of UNICEF for the year 2019 for nine Sub-Saharan countries, and based on the methods used, five criteria have been selected for consideration. Those of mothers in higher education were identified as having a higher weight, which means that this can affect positively the ability of mothers to mitigate the situation of FTT and protect their children. Results: The findings of the study highlight the factors of maternal education at a higher level and unhealthy habits as those with the greatest weight and impact on the FTT. Moreover, the results indicate that the association between maternal education, and especially higher education, and FTT is stronger in Ethiopia. Despite the limited amount of research on the specified relationship in Sub-Saharan countries, this study is among the initial ones to examine it. Conclusions: The current study can aid policymakers in devising appropriate policies and implementing effective measures to tackle FTT in Sub-Saharan Africa, like enhancing the number of mothers in these countries to be integrated into the educational system to help both themselves and their children mitigate or avoid the symptoms of FTT.